PENERAPAN DUE PROCESS MODEL TERHADAP TERSANGKA PADA MASA PANDEMI COVID 19 DI POLRES CILEGON - Ridwan Ridwan; Ahmad Lanang Citrawan; Belardo Prasetya Mega Jaya; Fanny Khalifatu Zanah; Khoiruttamam Khoiruttamam; Anisa Lutfiah; Norma Risca Pratiwi (Trunojoyo Madura University, 2023)
Article 1 point 2 of the Criminal Procedure Code states that investigations must be carried out based on this law (KUHAP) wherein the Criminal Procedure Code regulates evidence in the form of statements not confessions, where evidence may not be subject to violence, both physical and psychological, for this reason an examination is required with using the Due Process Model. This study uses a qualitative method with a normative juridical approach. Operationally it was carried out by library research and field studies at the Cilegon Police Station. The results of this study are that the examination of suspects carried out by investigators at the Cilegon Police Precinct before the Covid-19 pandemic was carried out professionally using the Due Process Model inspection system. Likewise, the examination of suspects during the Covid-19 pandemic, where the application of responsive law in an examination in the context of fulfilling the suspect's rights so that his case is immediately examined with a guarantee of justice which is part of the legal service or legal services.